The extensive and intensive margins of time investments on the skill development of children and adolescents - TAN, Yi Rachel (Institutional Knowledge at Singapore Management University, 2019)
The literature on time investments and skill development has focused on estimating the intensive margins of time investments; This study explores whether including extensive margins might provide additional insights. The extensive and intensive margins of maternal time investments and child time investments (or child self-investments) in three categories of activities (educational, structured and unstructured) on the cognitive and non-cognitive skill development of children (6 to 10 years) and adolescents (11 to 15 years) are quantified by fitting skill production functions with ordinary least squares and family fixed effects specifications. Cognitive skills are assessed by three achievement test scores which indicate the children’s vocabulary level along with their passage comprehension and mathematical abilities. Non-cognitive skills are assessed by indexes which measure the children’s problem behaviours and emotional/social abilities. Results indicate that including the extensive margins of time investments is beneficial as they influence cognitive skill development. Furthermore, there are instances where the extensive and intensive margins act in opposite directions. For example, adolescents who engage in educational activities independently (make self-investments in educational activities) during childhood have higher comprehension skills than those who do not (i.e. positive extensive margin). However, they have lower comprehension skills with every additional hour invested (i.e. negative intensive margin). While cognitive skills are affected by time investments, non-cognitive skills are generally not significantly affected by time investments. Since this is the case, the remainder of the analysis concentrates on cognitive skill development. A subgroup analysis reveals that time investments affect gender sub-groups and racial sub-groups differently, suggesting that gender and family background factors influence the effects of time investments. In addition, there is evidence that paternal time investments affect cognitive skill development.